2020
DOI: 10.1101/2020.04.03.023341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estrogen exacerbates mammary involution through neutrophil dependent and independent mechanism

Abstract: 21There is strong evidence that the pro-inflammatory microenvironment during post-partum 22 mammary involution promotes parity-associated breast cancer. Estrogen exposure during 23 mammary involution drives tumour growth through the activity of neutrophils. However, how 24 estrogen and neutrophils influence mammary involution are unknown. Combined analysis of 25 transcriptomic, protein, and immunohistochemical data in Balb/c mice with and without 26 neutrophil depletion showed that estrogen promotes involution… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Neutrophils are known to undergo epigenetic changes during development and under mature state in response to environmental cues [31][32][33]. We have also reported that neutrophils in the post-weaning and nulliparous mammary tissue respond to estrogen differently [28]. Whether the innate immune function of neutrophils is generally compromised by tumour burden requires further investigation.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Neutrophils are known to undergo epigenetic changes during development and under mature state in response to environmental cues [31][32][33]. We have also reported that neutrophils in the post-weaning and nulliparous mammary tissue respond to estrogen differently [28]. Whether the innate immune function of neutrophils is generally compromised by tumour burden requires further investigation.…”
Section: Discussionmentioning
confidence: 90%
“…This difference in functional outcomes may be attributed to the difference in the tissue microenvironment. The pro-in ammatory microenvironment in the mammary gland of Inv mice facilitates estrogen-induced neutrophil recruitment and reprograming [15,28], leading to the release of pro-tumoral cytokines/chemokines. This is in contrast with Null mice in which, estrogen is generally anti-in ammatory in the mammary tissue [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Endometriosis is known to be estrogen-dependent, and local estradiol biosynthesis in endometriotic lesions combines with peritoneal inflammation in the peritoneal cavity to form an abnormal immune-endocrine microenvironment [1]. In breast tissue, estrogen function supports neutrophil infiltration and neutrophil-mediated adipocyte regeneration [80]. In the early phases of endometriosis, estrogen (E2) and estrogen receptor (ER) are essential for immunological regulation and angiogenesis [79], and the physiological connection between estrogen-induced modifications in neutrophil function and endometriosis pathogenesis is of particular interest.…”
Section: Neutrophils In Mouse Models Of Endometriosismentioning
confidence: 99%